1976
DOI: 10.3758/bf03199396
|View full text |Cite
|
Sign up to set email alerts
|

Two forms of retinal disparity

Abstract: The retinal disparities in stereograms where the vertical alignment of pairs of homologous points in one eye differs from that in the other eye were found to be more effective than disparities that do not involve that kind of binocular difference. The presence of such "transverse disparities" was found to shorten the time elapsed until perceived depth was reported in four instances. in two simple stereogram pairs and in two different pairs of random dot pattern stereograms. In .an experiment where binocular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 4 publications
4
25
0
Order By: Relevance
“…Thus, only the different forms of the binocular configurational difference could have been responsible for the different results in these experiments (Wallach & Bacon, 1976).…”
Section: Redundant Stimulation In Stereoscopic Visionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus, only the different forms of the binocular configurational difference could have been responsible for the different results in these experiments (Wallach & Bacon, 1976).…”
Section: Redundant Stimulation In Stereoscopic Visionmentioning
confidence: 87%
“…But a particular distance difference is configurationally more conspicuous when the absolute distance between the images is short rather than long. Lindauer and I (Wallach & Lindauer, 1962) found that identical disparities resuited in larger perceived depth when they were associated with shorter absolute distances than with larger absolute distances. The more conspicuous configurational differences produced greater depth.…”
Section: Redundant Stimulation In Stereoscopic Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallach and Bacon (1976), and Gillam et al (1984,1988) found that the latency to perceive depth was longer when stimulus disparities were changing in a horizontal direction (creating expansion-compression patterns of disparity) than when they were changing in a vertical direction (creating shearing patterns of disparity). In Wallach and Bacon's (1976) first experiment, there is a larger component of orientation disparity present in the "transverse" disparity stimulus, which they reported was easier to see, than in their "superpositional" stimulus (their Fig. 2) which is essentially a horizontal expansion of one eye's view, and possesses only a small component of orientation disparity along the oblique.…”
Section: Discussionmentioning
confidence: 99%
“…St~~o~opi~ly-de~ned surfaces which slant or curve about a horizontal axis are often perceived more readily, and have more apparent slant or curvature, than surfaces which slant or curve about a vertical axis (Wallach & Bacon, 1976;Rogers & Graham, 1983;Gillam, Flagg 62 F&day, 1984;Gillam, Chambers 4% Russo, 1988;Rogers & Cageneifo, 1989;Mitch&on & McKee, 1990;Mitchisan & Westheimer, 1990;Gillam 8z Ryan, 1992). Although there are signif?cant individual differences in the magnitude of the effect, studies of the anisotropy have shown that surfaces containing disparities that change in a direction orthogonal to the axis joining the two eyes [i.e.…”
Section: Introductionmentioning
confidence: 99%